Streptomyces as Microbial Chassis for Heterologous Protein Expression - Hwang, Soonkyu; Lee, Yongjae; Kim, Ji Hun; Kim, Gahyeon; Kim, Hyeseong; Kim, Woori; Cho, Suhyung; Palsson, Bernhard O.; Cho, Byung-Kwan (Frontiers in Bioengineering and Biotechnology, 2021)
Heterologous production of recombinant proteins is gaining increasing interest in biotechnology with respect to productivity, scalability, and wide applicability. The members of genus Streptomyces have been proposed as remarkable hosts for heterologous production due to their versatile nature of expressing various secondary metabolite biosynthetic gene clusters and secretory enzymes. However, there are several issues that limit their use, including low yield, difficulty in genetic manipulation, and their complex cellular features. In this review, we summarize rational engineering approaches to optimize the heterologous production of secondary metabolites and recombinant proteins in Streptomyces species in terms of genetic tool development and chassis construction. Further perspectives on the development of optimal Streptomyces chassis by the design-build-test-learn cycle in systems are suggested, which may increase the availability of secondary metabolites and recombinant proteins.